Floods after drought: storytelling with agro-pastoralists in a Kenyan dryland - Weesie, Ruben V.; Rohse, Melanie; Van Loon, Anne F.; Koehler, Johanna; Barendrecht, Marlies H.; Mwangi, Moses (Frontiers in Water, 2025)
In East African drylands, agro-pastoralists are continuously dealing with recurrent droughts and floods damaging to their livelihoods. Although droughts and floods have been widely studied as separate phenomena, little attention has been paid to agro-pastoral experiences of the relations between successive droughts and floods over time. Yet when floods follow a drought, they are likely to exacerbate or alleviate the impacts of the preceding drought. To address this, we conducted a study in southeastern Kenya’s drylands, organizing storytelling sessions with 213 agro-pastoralist participants. By reconstructing a history of droughts and floods experiences from the 1940s to the early 2020s, we found that droughts and floods are strongly interrelated and ambivalent phenomena. During the latter half of the 20th century, agro-pastoralists narrated droughts as severely disruptive, distinct periods that frequently concluded with flooding, which both alleviated and intensified drought impacts. In the 21st century, however, droughts and floods are no longer experienced as discrete, named events but rather as a new normal. Floods after drought have become more frequent, short-lived, intense, and erosive, their regenerative function diminishing. The participants articulated how they adapt to droughts and floods amidst rapid socio-economic and socio-environmental changes. We found that various drought adaptation measures, largely initiated by (non)governmental organizations operating in drylands, have introduced flood risks. As droughts and floods are expected to become even heavier and frequent in future East African drylands and beyond, the stories underscore a need for adaptation approaches that benefit from the regenerative potential of floods after drought.